解方程 要过程 5(x+2)=2(5x+1) 3(x-2)+1=x-(2x-1) -5(x+1)=1⼀2 1-3(2-x)=0 4-x⼀3=x-3⼀5-1

x-x-1/2=2-x+2/5
2024-11-26 08:14:08
推荐回答(3个)
回答1:

5(x+2)=2(5x+1)
5x+10-10x-2=0
5x=8
x=8/5
3(x-2)+1=x-(2x-1)
3x-6+1-x+2x-1=0
4x=6
x=3/2
-5(x+1)=1/2
-5x-5=0.5
5x=-4.5
x=-0.9
1-3(2-x)=0
1-6+3x=0
3x=5
x=5/3
4-x/3=x-3/5-1
60-5x-15x+9+15=0
20x=84
x=4.2

回答2:

5(x+2)=2(5x+1)
5x+10=10x+2
5x=8
x=8/5
3(x-2)+1=x-(2x-1)
3x-6+1=x-2x+1
4x=6
x=3/2

-5(x+1)=1/2
-10x-10=1
10x=-11
x=-11/10

1-3(2-x)=0
1-6+3x=0
3x=5
x=5/3

4-x/3=x-3/5-1
5(4-x)=3(x-3)-15
20-5x=3x-9-15
8x=44
x=11/2

x-x-1/2=2-x+2/5
10x-5(x-1)=20-2(x+2)
10x-5x+5=20-2x-4
7x=11
x=11/7

回答3:

5(x+2)=2(5x+1)
5X+10=10x+2
-5X=-8
x=8/5
3(x-2)+1=x-(2x-1)
3X-6+1=-x+1
4x=6
x=3/2
-5(x+1)=1/2
-5x-5=1/2
-5x=11/2
x=-11/10
1-3(2-x)=0
1-(6-3x)=0
-5+3x=0
x=5/3
4-x/3=x-3/5-1
-4x/3=-28/5
x=21/5